A least-cost greenfield planning method for small-scale remote area power systems - Dimal, Aimar Jay E.; Pedrasa, Michael Angelo A. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
Multiple works have been conducted in planning for rural electrification which usually differ by methodology, application, integration scheme, optimization technique, and component modeling. However few studies focus on comprehensive greenfield planning that includes design of generation down to the associated delivery systems. Such problems are combinatorial in nature, hence global optimum can only be approximated through the use of multi-stage optimization processes, heuristic techniques, or solvers of mathematical formulations. This study develops a method of designing a least-cost power system for a rural community Setting. The process includes identifying which among the demand points are supplied through microgrid or individual systems, designing the network Configuration with selection of appropriate conductors, and placement and identification of generation sources. The method is divided into two stages: (1) clustering of demand points and placement of generation source, and (2) identifying the best generation source combination and design of the associated delivery systems. The developed procedure was applied to a 99-demand point test system with rural area characteristics to determine the least-cost power system design. The method was also applied to explore the behavior of the least-cost solution with varying generation costs, spatial distribution of demand points, and distances between demand points.
Thesis (M.S. Electrical Engineering)--University of the Philippines Diliman
Keywords: Electric power systems -- Planning; Rural electrification; Remote area power supply systems